Valoración de Bancolombia a través de diferentes metodologías (2014)
"The structure of the balance sheet of a financial institution is quite different from a company of the real sector, therefore, the focus of its valuation must be performed from a different perspective.In this work we calculated the equity value of Bancolombia through market multiples, dividend discounted model and excess of returns model. For the development of previous models was appropriate to use cost of equity of Bancolombia involving the country risk in its calculation." -- Tomado del Formato de Documento de Grado.